United States Normative Attitudes for Pursuing Parenthood as a Function of Gender, Sexual Orientation, and Age - Tate, Doyle P. (Frontiers in Psychology, 2022)
Decisions about whether or not to become a parent are significant parts of normative human development. Many studies have shown that married different-sex couples are expected to become parents, and that many social pressures enforce this norm. For same-sex couples, however, much less is known about social norms surrounding parenthood within marriage. This study examined injunctive norms and descriptive norms for the pursuit of parenthood as a function of age, gender, and sexual orientation. Participants in an internet survey included 1020 (522 heterosexual, 498 lesbian/gay) cisgender people from across the U.S. Findings showed that norms, especially descriptive norms, for the pursuit of parenthood for heterosexual people were much stronger than those for lesbian women and gay men, and that norms for lesbian women were stronger than those for gay men. These differences were more pronounced for older, heterosexual, and male participants. However, lesbian and gay participants, especially gay men, reported that lesbian and gay people ought to become parents to the same extent as heterosexual people. Overall, the results indicated that, regardless of sexual orientation, adults report that lesbian and gay married people ought to become parents, but that they expect only a minority of these couples will pursue parenthood. This research provided a glimpse into how Americans are envisioning family formation among same-sex couples today.